O papel da família na participação de crianças e adolescentes em atividades físicas e esportivas - Pimentel, Alex Viana (Brasil, 2023)
Adolescence is a period of life in which intense physical and psychological changes occur, and in this phase habits can be determined that will remain in adult life, such as the practice of physical activities and eating habits. Studies show that children and adolescents whose parents or guardians are physically active are more likely to participate in regular physical and sports activities. Therefore, at this stage, parental support is important for the healthy development of the child or adolescent. The objective of the study was to synthesize the existing evidence on the role of the family (parents, guardians or caregivers) in encouraging and participating children and adolescents in physical and sports activities. An integrative literature review was performed that included studies that met the following inclusion criteria: studies published between 2016 and 2021, written in Portuguese, English or Spanish. As a search strategy, the main databases in research in the area of health sciences were used (VHL-Virtual Health Library, Capes Dissertation Bank, Scopus and Google Scholar), and the terms used for the search included 4 groups of descriptors (Lifestyle, physical activity, social support and children, adolescents).The evaluation of the studies found was carried out by two researchers who read the titles and abstracts in the first stage and the complete manuscript of the studies that met the inclusion criteria. For the analysis of the results, the codification and evaluation of the quality of the publications of the data synthesized in tables that present the methodology characteristics, main results found were made. The initial search resulted in 576 results. After reading the titles and abstracts, 21 publications were selected for full reading.After reading the studies in full, only eight articles were selected to continue the research. In temporal terms, of the eight articles selected, one was published in 2015; one in the year 2017; one in the year 2018; five in the year 2021.Of the analyzed articles, three were published in Portuguese, referring to studies carried out in Brazil (South America), five were published in English, three of which were developed in North America (two in the USA and one in Canada), and the other two publications in Europe (Germany and Sweden), no articles were found in Spanish.As for methodological aspects, seven studies used a quantitative approach and only one with a qualitative approach. In general, research has shown that children and adolescents are strongly influenced by their parents in relation to the practice of physical activity or sports, the study shows that adolescents whose parents practice physical activity during childhood are more likely to be physically active. Therefore, research has shown that parents play a fundamental role in the behaviors and habits related to the practice of physical activity of their children, either as financial and social support, or even as motivators for the practice, when it is performed with the child.